Coherent and incoherent photon-assisted electron tunneling in optoelectronic molecular devices in soft solids - Bodyfelt JD; Dahnovsky Y (Massey University)
An electron in a bath with slow degrees of freedom (such as soft solids, e.g., proteins) is driven by a strong time-dependent electric field. In this molecular device, the electron dynamics are characterized by quasicoherent oscillations with slow square-root decay even at room temperatures. The frequency of the oscillations and the equilibrium distribution are found essentially to depend on the field intensity and the medium parameters. The applied field effectively changes the relaxation time of the environment from fast to slow and vice versa. The quasicoherence allows for the prevention of overheating in the microdevice. It is also shown that the applied field is capable of changing the character of the electron dynamics from quasicoherence to incoherent decay. The electron transition probability strongly depends upon the applied voltage (bias) and at some values of the field parameters, this voltage can quickly switch the coherent transfer over to incoherent transfer and vice versa. Despite the slow electron transfer in the incoherence region, the equilibrium distribution can favor either products or reactants, depending upon the field intensity. In the incoherent regime, the electron localization is possible. All these features can be exploited in microcomputers or quantum computers.